Identification and characterization of biofilm-producing clinical isolates of staphylococcus aureus - Atshan, Salman Sahab (2013)
Staphylococcus aureus is considered the major etiological agent of human infections. It is a biofilm-forming bacterium, which embedded itself in a matrix of extracellular polysaccharide (slime), and facilitates the adherence of these microorganisms to biomedical surfaces causing many persistent infections. The main issue with biofilm has become a global public health problem that is impacted by the insufficient management of patients infected with biofilm growth as extremely adaptable to antibiotic pressure. The ability of S. aureus to form biofilm is a long-known fact but the problem involving the issue of biofilm identification has remained since the availability of the phenotypic approach of growth on highly selective or differential media can provide identification of biofilm formation but with a high margin of error through many false negative outcomes. In line with these shortcomings, the present study embarked on several strategies to overcome the issue of inaccurate biofilm identification through the development of an improved method that can provide positive identification. In this study, it was found that our modified-Congo red agar was significantly different from published-CRA (P <0.05). The modified agar constituents provided not only stable 100% formation of black,also showed very high correlation with standard methods and with the presence of icaADBC biofilm genes. In the second part of the work, the ability to adhere and produce biofilms of genotypically different clones of S. aureus was characterised. The study found the isolates that belonging to similar spa, SCCmec and ST types have similar abilities to produce biofilms. Moreover, isolates that have different spa types showed high variation in their ability to produce biofilms.The results indicate that differences in biofilm production capacities are caused by the differences in surface protein A (spa) type and are not due to differences in MLST and SCCmec types. In the third part of the work, the prevalence and distribution of microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) and biofilms genes in different clones of S. aureus were determined. the study found icaADBC,fnbA, eno, ebps, clfA and clfB genes to be present with a high prevalence and were equally distributed between the various clone types of 60 MSSA and MRSA clinical isolates, while the prevalence of other MSCRAMM genes were found to be variable. In the fourth part of the work, the transcriptional profiles of specific staphylococcal genes encoding MSCRAMMS and icaADBC were determined during gradual changes in complexity of the biofilm production under different growth phases. The results indicate that the relative expression of MSCRAMMS and icaADBC genes in comparison with the phenotypic biofilm morphology can be utilized as a model to study the up- and down- regulation of such genes. Delayed expression of certain genes during stationary phase biofilms grown at significantly higher levels are considered important for biofilm development and for the survival of composing cells in a nutrient-scarce niche. In the fifth part of this work, the extracellular 2DE protein profiles among genotypically different clone types and under different time-points of biofilm developed growth of S. aureus were characterized. The main results of 2DE studies showed a high degree of extracellular protein heterogeneity among the various clone types and under different time-points growth, indicating that different regulation modes of growth processes are operating under different clone types and under altered time conditions. In the sixth part of this work, the antimicrobial susceptibility patterns (glycopeptide, B-lactam, lipopeptide,oxazolidinones and glycylcycline) of different S. aureus clone types were determined. The results revealed that MICs and the bactericidal activities of these agents’ classes within the different spa types were largely different. However, the MIC and MBC among clones within the same spa and MLST type were slightly different. Moreover, the minimum biofilm reduction concentrations (MBRCs) of these agents in the prevention of biofilm formation in vitro were overall greater than the CLSI-defined planktonic MIC breakpoint for resistance and quite variable among different clone types. The diversity in the antibiotic susceptibilities of isolates within the various clone types emphasises the need for continuous monitoring for the clones and clinicians should consider a correct antibiotic rather than empirical treatment. In the last part of this study, the effect of sub-inhibitory concentrations of vancomycin and tigecycline on the steady-state mRNA transcription levels of MSCRAMM and the icaADBC target gene, as well as on secretion of exoproteins of different clone types of S. aureus isolates were studied. The results indicate that the effects of these antibiotics generally affecting all virulence factors of selected target genes and the secretion of exoproteins. Thus might enhance the virulence of this bacterium, therefore using these antibiotics to treat S. aureus infections may contribute to unpredictable results. Conclusion: We conclude that a considerable difference exists among similar and various clone types of S. aureus. This variation could have contributed to the degree of virulence even within the same clone and enhanced heterogeneity in the infection potential. Thus, new genetic diversity suggests that the development of a rapid and precise identification profile for each clone type in human infections is very important to prescribe appropriate antibiotics and reduce the empirical treatment.